1995
DOI: 10.1002/anie.199504741
|View full text |Cite
|
Sign up to set email alerts
|

Photo Electron Transfer Induced Macrocyclization of N‐Phthaloyl‐ω‐aminocarboxylic Acids

Abstract: COMMUNICATIONSdeveloping negative charge is stabilized by the cationic metal center, while in the latter case the developing negative charge is not stabilized by the metal. The metal center in 4 is providing double Lewis acid activation, while the metal center in 5 is providing single Lewis acid activation. We recently showed that a dinuclear metal complex can rapidly cleave an RNA model compound by providing double Lewis acid activation.['] The two methyl groups in the neocuproine ligand should decrease the 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…In the case of baskets functionalized with hydrophobic α‐amino acids, we found that the photo‐induced loss of CO 2 would render these hosts insoluble in water to prompt their precipitation. With six carboxylates within 1 6− , however, we wondered if a light stimulus would trigger their removal to give baskets possessing distinct recognition characteristics and/or solubility (Scheme B). In fact, when N ‐phthaloyl‐glutamic acid 5 2− (10 m m phosphate buffer, pH 7.0) was exposed to 300 nm light (Scheme A) there followed the exclusive formation of cyclized product 6 (Figure S13) .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the case of baskets functionalized with hydrophobic α‐amino acids, we found that the photo‐induced loss of CO 2 would render these hosts insoluble in water to prompt their precipitation. With six carboxylates within 1 6− , however, we wondered if a light stimulus would trigger their removal to give baskets possessing distinct recognition characteristics and/or solubility (Scheme B). In fact, when N ‐phthaloyl‐glutamic acid 5 2− (10 m m phosphate buffer, pH 7.0) was exposed to 300 nm light (Scheme A) there followed the exclusive formation of cyclized product 6 (Figure S13) .…”
Section: Resultsmentioning
confidence: 90%
“…With six carboxylates within 1 6− , however, we wondered if a light stimulus would trigger their removal to give baskets possessing distinct recognition characteristics and/or solubility (Scheme B). In fact, when N ‐phthaloyl‐glutamic acid 5 2− (10 m m phosphate buffer, pH 7.0) was exposed to 300 nm light (Scheme A) there followed the exclusive formation of cyclized product 6 (Figure S13) . On the basis of the literature, we speculate that the formation of long‐lived 3 ππ* triplet state of the phthalimide chromophore from 5 2− triggers the removal of α and γ carboxylates to give diradical intermediate which then cyclizes into racemic 6 (the Norrish–Yang reaction).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of macrocyclic ring systems was also possible in this way; thus, azacyclotridecane (n = 9) and a 26-membered cyclic dipeptide could be generated in 60% yield from the readily available N-phthaloylamino acid [27]. The synthesis of macrocyclic ring systems was also possible in this way; thus, azacyclotridecane (n = 9) and a 26-membered cyclic dipeptide could be generated in 60% yield from the readily available N-phthaloylamino acid [27].…”
Section: Fused Isoindolones Containing One N Atommentioning
confidence: 99%
“…This primary photoproduct was stable when directly excited or tripletsensitized, however, in the presence of base it rapidly cyclized with extrusion of CO 2 to give the benzopyrrolizidine 7. 17 Water was necessary as cosolvent in order to suppress the formation of reduction products simply formed by CO 2 /H-exchange (vide infra).…”
Section: Decarboxylative Photoyclizations Of Phthalimidesmentioning
confidence: 99%